Internalisasi Nilai-Nilai Disiplin Siswa di SDN Taman Pagelaran Kabupaten Bogor - Yanti Yulianti (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to determine the internalization of students' disciplinary character values at SDN Taman Pagelaran Bogor Regency. The approach used in this study is a qualitative approach with a phenomenalogical type of research. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis techniques are carried out through data reduction, data display, and verification. The results showed that: 1.) The efforts of SDN Taman Pagelaran Bogor Regency in improving the character of student discipline are starting from a school policy, the enforcement of the rules of SDN Taman Pagelaran Bogor Regency, discipline by forming a disciplinary enforcement team, instilling discipline awareness in students by applying discipline attitudes every day so that it becomes a habit, instilling a disciplined character through several activities; 2.) The implementation of internalization of students' disciplinary character values at SDN Taman Pagelaran Bogor Regency is instilled through several activities including: Introduction Week, Monday ceremony, morning tadarus and extracurricular; 3.) The results of internalizing the disciplinary character of students at SDN Taman Pagelaran Bogor Regency are: students are more orderly &aware of discipline and the activities of SDN Taman Pagelaran Bogor Regency run smooth.